Influence of Nutrient Media Compared to Human Synovial Fluid on the Antibiotic Susceptibility and Biofilm Gene Expression of Coagulase-Negative Staphylococci In Vitro - Steixner, Stephan Josef Maria (Antibiotics (Basel), 2021)
Bacterial antibiotic resistance and biofilm formation are mechanisms usually involved in the pathogeny of implant-related infections. Worldwide, antibiotic susceptibility tests are usually carried out using nutrient-rich media. Clinical routine laboratories and even research centers use for example EUCAST or CLSI for guidelines. In this study, we investigated the effect of different nutrient media on the antibiotic susceptibility and icaADBC gene expression of bacteria in biofilm. As media, Müller-Hinton Bouillon (MHB), Tryptic Soy Broth (TSB) and human synovial fluid (SF) diluted 1:4 in phosphate buffered saline (PBS), each also supplemented with 1% glucose, were used. The influence of different nutrient media on the antibiotic susceptibility of coagulase-negative staphylococci (CoNS) was evaluated by counting of colony-forming units (CFU) and by checking the metabolic activity of the bacteria. We used reverse transcriptase and real-time qPCR to investigate the influence of nutrient media on the biofilm gene expression. We used two-way analysis of variance (ANOVA). p < 0.05 was considered to be statistically significant. Significant differences in growth and antibiotic susceptibility were detected in all strains tested among the different media used. The nutrient media showed influence on the cell viability of all bacteria after antibiotic treatment. IcaADBC gene expression was significantly influenced by glucose and all nutrient media. The results highlight the influence of glucose on the antibiotic susceptibility, growth and gene expression of all strains tested. For all strains, a significant difference in bacterial recovery, viability and gene expression were found when compared to biofilm grown in SF.